Microfinance environment in Uzbekistan: Analysis of supply and demand - Nargiza Alimukhamedova (Institut für Ost- und Südosteuropaforschung (IOS), 2014)
The paper describes the microfinance environment in Uzbekistan, with an emphasis on two types of non-bank microfinance institutions - Credit Unions and Microcredit Organizations. The specific nature of these institutions provides new evidence of the commercially oriented microcredit model and SME lending, which is an emerging trend in mainstream microfinance. The paper offers two important contributions. On the supply side of microcredits, we analyse the determinants of initial placement of these MFIs in districts of Uzbekistan. We find that MFIs follow general economic principles when choosing the location for establishment. On the demand side, we analyse the actual margins of excess demand for microcredits by considering only the pool of eligible applicants. We find that the total probability of microcredit approval is on average only 0.5, which implies that the actual margins of untapped market could be just half of that projected when the narrow definition of eligible applicants is taken into account.
urn:nbn:de:101:1-2014101419551
Keywords: O16; C34; 330; microcredit; microfinance institutions; credit unions